Nuptiality in Buenos Aires in the mid-twentieth century: Chascomús, La Plata and San Martin - Masciadri, Viviana (Papeles de Población; Vol. 23 Núm. 92 (2017), 2018)
This research analyzes nuptiality trends around 1947 and 1960 in Buenos Aires (Argentina) and three of bonaerenses districts. First this research describes the demographic policies related to nuptiality. Then the study analyzes the statistics of marriages and the structure of the population by sex, age and marital status according to the census definition. It also describes the subpopulation that voluntarily disassociated from a cohabitation or marriage based on the relative distribution as well as the probability of being divorced in 1947 and separated / divorced in 1960. This cross-cutting perspective contextualizes the trends in the constitution and dissolution of unions. The paper concludes that secularization had not been completed in the mid-twentieth century; in fact, the demographic policies demanded that the nuptiality was the expression of economic policies founded on the natural order of things.